Vasco da Gama and the linking of Europe and Asia - Disney, Anthony (Ed); Booth, Emily (Ed) (New Delhi Oxford University Press, 2000)
Vaco da Gama and the linking of Europe and Asia is collection of essays re-evaluates Vasco de Gama,s voyage, its economic cultural, political and religion implication. Portugal made only a marginal impact on the world of the Indian Ocean. The Portuguese i
Keywords: Vasco da Gama-Jorneys; Voyages and travels; International trade; International economic relations; Civilization; Europe-History; Asia-History